Stability Analysis of Traction Rubber Pile for Bogie - Anzhou JING; Guangwu YANG; Shoune XIAO; Bing YANG; Tao ZHU (机车电传动)
By using the rubber constitutive equation named Mooney-Rivlin model, the load-bearing performance of the traction rubber pile for the bogie was analyzed by LS-Dyna, and the "force-displacement" curve(that is, three-way stiffness of rubber piles),were obtained on longitudinal, transverse and vertical loads. The calculation results are in good agreement with the test, and the relative errors are about 10%, which verifies the accuracy of the simulation method. By comparing the influence of different hardness on the stability of rubber pile under longitudinal displacement, the critical longitudinal displacement of the traction rubber pile is 35.2 mm when the hardness is 48 HA, and the longitudinal bearing capacity is the best when the hardness is 46 HA. Assembly directions also have great influence on its forms of instability. The installing form which use short side in parallel with clamping long side is suggested for traction rubber pile.